Constrains for seeking perimenopausal healthcare services among women aged 40–60 years in Guangzhou, China: a cross-sectional study - Wang, Yiding; Liu, Yan; Xiong, Ribo (Frontiers in Public Health, 2025)
IntroductionIn China, the vast majority of perimenopausal healthcare (PMH) services are performed in a diversity of outpatient clinics, such that women may encounter more obstacles toward acquiring appropriate management of perimenopause, resulting in misdiagnosis or missed diagnosis and subsequent repeated visits. Establishing a specialty clinic for perimenopausal women is a new concept. This study aimed to assess PMH services utilization among women aged 40–60 years, and identify factors influencing it's uptake in Guangzhou, China.MethodsA cross-sectional study was conducted from February to October 2024 including 1,136 women from Tianhe District, Guangzhou. Barriers and facilitators for PMH services utilization were analyzed based on Andersen's Behavioral Model of Health Services Use.ResultsThe magnitude of PMH services utilization was 31.0% among women aged 40–60 year in Guangzhou, China. Factors associated with services utilization included immigrant women (OR = 3.158, 95%CI:2.014–3.957), not living closer to the PMH clinic (OR = 2.841, 95%CI:1.784–3.259), women with limited decision-making autonomy regarding PMH services utilization (OR = 0.361, 95%CI:0.128–0.813), having a feeling of stigma toward perimenopausal health problems (OR = 0.284, 95%CI:0.079–0.560), poor social support (OR = 3.015, 95%CI: 1.809–3.217) and moderate/severe menopausal symptoms (OR = 2.045, 95%CI:1.610–2.967 and OR = 1.836, 95%CI:0.739–2.318, respectively).DiscussionThe utilization of PMH services among women aged 40–60 years remained suboptimal. Efforts should be made to raise public concerns about perimenopause. Improving services access is critical for increasing the utilization of PMH services.